Phase shift of isospin-2 pi pi scattering from lattice QCD - PEARDON, MICHAEL; THOMAS, CHRISTOPHER (My University, 2011)
Finite-volume lattice QCD calculations offer the possibility of extracting resonance parameters from the energy-dependent elastic phase-shift computed using the Luscher technique. In this letter, as a trial of the method, we report on the extraction of the nonresonant phase-shift for S and D-wave pi pi isospin-2 scattering from dynamical lattice QCD computations. We define a variational basis of operators resembling pairs of pions of definite relative momentum and extract a spectrum of excited states that maps to phase-shifts at a set of discrete scattering momenta. Computations are performed with pion masses between 400 and 520 MeV on multiple spatial volumes. We observe no significant quark mass dependence in the phase-shifts extracted which are in reasonable agreement with the available experimental data at low momentum.
PUBLISHED
Keywords: Particles and fields physics; pi pi isospin-2 scattering